The General Principles of The Curriculum In Some Manuscripts Arab And Muslim Scholars - فاطمة زبار عنيزان (College of Education for Women, 2019)
Our scientists Arabs old efforts in achieving texts that led to the foundations of general rules they have set for this work in accordance with the systematic context is based on the study, analysis and precision in dealing with this work, which became the basis for each investigator to the present day, which was to them careful consideration manuscripts and work to be closer to the image by its author, so produced their efforts in this area several books provided the technical wizards of this science, which did not leave a gap in which only gave her treatments and suggestions each and every one of the point made by and gave her what produced the expertise in this direction in accordance with the formulations methodology are balancing and application, any that Makedmoh such as advanced stage in the art of the investigation, who settled and clarified its features on their hands which they put the primary application for this work, including the rules: the interview between copies, Repair error and evaluate the melody and the treatment of miscarriage increases and settings, shape, making notes, writing and calligraphy and finally attention tool writing Pen..